Visible, Indigenous, and Gender Minorities among Canadian Jews, 2021 - Brym, Robert (Canadian Jewish Studies / Études juives canadiennes, 2024)
This paper focuses on Canadian Jewish minorities that have attracted little scholarly attention. It does so mainly by reviewing data from the 2021 Canadian census on Jews who identify as members of visible, Indigenous, and gender minorities. This discussion points to several areas in need of further academic research, and concludes by claiming that, ironically, understudied Canadian Jewish minorities (including but not restricted to those discussed here) may form a majority of Canada’s Jewish population, making their inclusion in community affairs a necessity for the continued social cohesion of the country’s Jewish community.